Importance of ice algae versus phytoplankton in the diet of megabenthic organisms under contrasting sea ice conditions (Canadian Arctic): a dual biochemical approach (SIA and HBIs) - Combaz, Thibaud; Witte, Ursula; Brown, Thomas A.; Archambault, Philippe (Frontiers in Marine Science, 2025)
The effects of global warming are most pronounced at high latitudes and are a threat to primary productivity patterns and, in particular, to sea ice algae. Here, we investigated the importance of ice algae in the diet of megabenthic organisms belonging to several feeding guilds across several locations in the Canadian Arctic characterised by different sea ice conditions using two biochemical approaches i.e., stable isotope and highly branched isoprenoid (HBI) lipids analysis. In addition, the short-term ingestion (gut contents) versus mid to long-term assimilation (tissues) of carbon were investigated to depict momentary condition in the present and the recent past. Our results show firstly that, as soon as the ice breaks up, ice algae accounts for a high proportion of the organic matter deposited to the seafloor and can provide a substantial carbon input to benthic communities for a long period of time (up to 79 days after sea ice break up in our case). Overall, organisms responded rapidly and efficiently to this pulse of fresh organic matter but trends in resource utilisation (quality and quantity) were observed based on feeding strategy. Deposit feeders (except those from lasting sea ice cover) and predators/scavengers showed a dominance of ice algae feeding, while suspension feeder showed a stronger reliance on phytoplankton. Finally, the spatial variability in resource utilisation by ophiuroids is likely related to area’s specificities (e.g., primary production, ice break-up timing, grazer abundance) and highlighted their ability to adapt to available food by switching their feeding types. Our data show that sympagic (ice-associated) carbon represents a significant proportion of the carbon ingested by the megabenthic organisms in the Canadian Arctic during spring/summer but appears to be highly variable depending on sea ice conditions and availability (e.g., patchiness, depth) on the seafloor. Overall, the ongoing decline in seasonal sea ice could alter the functioning and dynamic of the benthic food web in the Canadian Arctic if certain feeding types (e.g., deposit feeders) are unable to adapt to a change in primary productivity patterns.